Forecasting with spatial panel data - Badi H. Baltagi; Georges Bresson; Alain Pirotte (Institute for the Study of Labor (IZA), 2009)
This paper compares various forecasts using panel data with spatial error correlation. The true data generating process is assumed to be a simple error component regression model with spatial remainder disturbances of the autoregressive or moving average type. The best linear unbiased predictor is compared with other forecasts ignoring spatial correlation, or ignoring heterogeneity due to the individual effects, using Monte Carlo experiments. In addition, we check the performance of these forecasts under misspecification of the spatial error process, various spatial weight matrices, and heterogeneous rather than homogeneous panel data models.
urn:nbn:de:101:1-2009070340
Keywords: C33; 330; Forecasting; BLUP; panel data; spatial dependence; heterogeneity; Prognoseverfahren; Panel; Räumliche Interaktion; Theorie